Sistem Informasi Manajemen Pengumpulan dan Pengangkutan Sampah Padat dengan Efisiensi Rute Menggunakan K-Means Clustering dan Travelling Salesman Problem - Munji Hanafi; Budi Warsito; Rahmat Gernowo (JSINBIS (Jurnal Sistem Informasi Bisnis), 2022)
The increasing population growth and rapid urbanization have resulted in large amounts of solid municipal waste (SMW). Nowadays, the problem of waste management is a problem that is being experienced by every country in the world. As a result, implementing efficient waste management strategies is increasingly needed. The collection and transportation of solid waste is the most important thing to pay attention to in waste management efficiency to reduce the costs of collecting and transporting solid waste. The research started by collecting data and interviewing the environmental services of Semarang City about the waste transportation system in Semarang City. The results of the data and interviews will then be used as a reference for the system analysis to be made. Then proceed with designing information systems. After that, the information system was developed by applying the Traveling Salesman Problem (TSP) method using a heuristic in the form of K-means Clustering. With the help of OR-Tools, TSP completion does not require node distance, just inputting the coordinates of each node. The study closed system testing. This research proposes a new approach to solving TSP. First is the process of assembling nodes into several clusters. Then, look for the shortest route in each cluster. The research resulted in 21 routes in 16 corridors to transport waste in Semarang City, presented on a map on a web-based Information System as Decision Support System (DSS). The comparison of the methods shows that TSP is the most suitable for this case.